2008
DOI: 10.1002/dvdy.21817
|View full text |Cite
|
Sign up to set email alerts
|

The unfulfilled/DHR51 gene of Drosophila melanogaster modulates wing expansion and fertility

Abstract: This is the first functional analysis in Drosophila of unfulfilled (unf; DHR51), the NR2E3 nuclear receptor superfamily ortholog of C. elegans fax-1 and human PNR. Both fax-1 and PNR mutations disrupt developmental events in a limited number of neurons, resulting in behavioral or sensory deficits. An analysis of two independent unf alleles revealed that unf mutants are characterized by one of two phenotypes. A proportion of the mutants eclosed but failed to expand their wings and were poorly coordinated. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 62 publications
4
29
0
Order By: Relevance
“…Previously, unf was shown to be essential for the wing expansion and fertility of adult flies, and abundantly expressed in the developing MBs [49]. Here we studied the function of unf in further detail and learned that unf acts in all three major types of MB neurons to promote proper neuron subtype identity and axon guidance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously, unf was shown to be essential for the wing expansion and fertility of adult flies, and abundantly expressed in the developing MBs [49]. Here we studied the function of unf in further detail and learned that unf acts in all three major types of MB neurons to promote proper neuron subtype identity and axon guidance.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to EcR , usp , and tll , we isolated unfulfilled ( unf ), the fly NR2E3 subfamily ortholog of C. elegans fax-1 and human photoreceptor-specific nuclear receptor ( PNR ) [48], [49]. unf has a novel function in MB development, and unf knockdown caused a severe MB lobe extension defect.…”
Section: Introductionmentioning
confidence: 99%
“…The unfulfilled ( HR51 ) gene was named on the basis of the mutant phenotype in which eclosed adults fail to unfold their wings and exhibit reduced fertility [167,168]. In mushroom bodies, it functions in specifying neuron identities and regulating axon pathfinding [169].…”
Section: Unf/fax-1/pnr (Nr2e3)mentioning
confidence: 99%
“…Unfortunately, the information about these genes is scarce. Recently, however, two independent DHR51 alleles have been characterized in D. melanogaster [158]. Consistent with the highly restricted expression of DHR51 in mushroom body neurons and in a small number of other cells of the central nervous system, DHR51 mutants displayed behavioural and sensory defects, including compromised fertility and coordination and wing expansion failure [158].…”
Section: Hr51 (Nr2e3) Hr83 (Nr2e5) and Nr2e6mentioning
confidence: 97%
“…Recently, however, two independent DHR51 alleles have been characterized in D. melanogaster [158]. Consistent with the highly restricted expression of DHR51 in mushroom body neurons and in a small number of other cells of the central nervous system, DHR51 mutants displayed behavioural and sensory defects, including compromised fertility and coordination and wing expansion failure [158]. Furthermore, it has been shown that DHR51 is a thiolate heme-binding protein and, as E75, binds NO and CO which suggests that this factor can also be a gas or a heme sensor [159].…”
Section: Hr51 (Nr2e3) Hr83 (Nr2e5) and Nr2e6mentioning
confidence: 99%